Re-Remembering Masuria in Reportage, Prose and Poetry - Mytych-Forajter, Beata (Porównania, 2025)
The article by Beata Mytych-Forajter Re-remebering Masuria in Reportage, Prose and Poetry is the result of searching for accounts of resettlements to Masuria and the relocation of its population in three books of different genres from the last decade (Beata Szady Wieczny Początek. Warmia i Mazury [Eternal Beginning. Warmia and Masuria]; Ishbel Szatrawska Toń [The Deep]; Marzanna Bogumiła Kielar Wilki [Wolves]). The reportage emphasizes the biographical facts of specific people, ethnographic details (architecture, religion) and new projects that found local identity. The historical and family novel, which contains fairy-tale and mythical themes, will emphasize the Eastern Borderlands as a part of the identity of the region’s inhabitants. The analyzed volume of poetry, however, highlights various (assimilation, isolation, creative solutions) techniques of dealing with resettlement from the south-eastern corners of Poland to Masuria.